2010
DOI: 10.1123/jpah.7.3.299
|View full text |Cite
|
Sign up to set email alerts
|

Walking Toward a New Me: The Impact of Prescribed Walking 10,000 Steps/Day on Physical and Psychological Well-Being

Abstract: Purpose:To determine whether individuals participating in a program designed to accumulate 10,000 steps/ day demonstrate health, fitness and psychological benefits.Methods:Sedentary individuals (22 F, 7 M; age 59.8 ± 5.78 yr) were randomly assigned into a walking (W, n = 14) or control (C, n = 15) group. Following baseline assessment, the W group was given a daily plan to reach 10,000 steps/day within 3 weeks and asked to maintain this level for 12 weeks; the C group was asked to maintain their current activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 0 publications
1
27
0
6
Order By: Relevance
“…Há evidências científicas relacionadas ao resultado positivo de um estilo de vida ativo, assim como, da participação em programas sistematizados de exercícios físicos, os quais previnem e amenizam os efeitos causados pelo envelhecimento (American College Of Sports Medicine [ACSM], 2009; Inoue et al, 2013;Morgan, Tobar, & Snyder, 2010).…”
Section: Participantesunclassified
“…Há evidências científicas relacionadas ao resultado positivo de um estilo de vida ativo, assim como, da participação em programas sistematizados de exercícios físicos, os quais previnem e amenizam os efeitos causados pelo envelhecimento (American College Of Sports Medicine [ACSM], 2009; Inoue et al, 2013;Morgan, Tobar, & Snyder, 2010).…”
Section: Participantesunclassified
“…Moderate intensity walking programs have been shown to attenuate functional fitness deterioration associated with aging (Morgan et al, 2010). Maintaining functional fitness helps older adults to continue to perform activities of daily living (personal care), and instrumental activities of daily living (shopping, preparing meals, driving, etc.…”
Section: Moderate Intensity Cut-off Pointsmentioning
confidence: 99%
“…Other studies have also shown that physical condition (balance, walking speed and lowerextremity strength) is important to the health and functional fitness in old age (Yamauchi, Islam, Koizumi, Rogers, Rogers, & Takeshima, 2005;Rogers, Sherwood, Rogers, and Bohlken, 2002;Morgan, Tabor, and Snyder, 2010). Functional fitness predicts the likelihood of older adults developing disease, disability, hospitalization, and mortality (Aoyagi, Park, Watanabe, Park, & Shephard, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…After twenty minutes of brisk walking by the average adult, endorphins will begin to be released and cardio-vascular and muscular fitness will begin to be built and felt (Lamb et al 2002). Walking outdoors is likely to involve the mood enhancing effects of daylight and thermoregulation, and increased social contact is also thought to lead to an enhanced sense of well-being and self esteem (Morgan et al 2010). Thus the endorphins and sense of well-being that are generated in the walking body are likely to contribute to a positive disposition in the walker and a greater likelihood of dispelling negative thoughts (Morgan et al 2010).…”
Section: Rapport and Positive Dispositionsmentioning
confidence: 99%